EFFECTIVENESS OF B3 WASTE MANAGEMENT OF CORONAVIRUS DISEASE 2019 (COVID-19) SELF-QUARANTINE - Veza Azteria; Ahmad Irfandi; Erna Veronika (Universitas Medan Area, 2022)
Patients who self-quarantine were carried out to break the chain from the spread of the COVID-19 virus, but a new problem arose: solid medical B3 waste originating from these patients. If this B3 medical waste is not managed properly, it can potentially transmit and be contaminated by infectious substances. Management of infectious waste from self-quarantine patients was minimal because most people did not know about it, and there was a lack of infrastructure from the government. Therefore the researchers were interested in researching the management of B3 waste, substantial B3 waste, from people who carried out Covid-19 self-quarantine. This study aimed to determine the community's effectiveness in managing solid medical B3 waste from COVID-19 self-quarantine activities. Using the snowball sampling method and cross-sectional design, the results showed that there was a significant relationship between Attitude (P Value = 0.000), Knowledge (P value = 0.006), Age (P Value = 0.019), Gender (P value = 0.000), Occupation (P value = 0.000) and Education (P value = 0.04) on community behavior in managing B3 medical waste during the Covid-19 self-quarantine period. Management of Solid B3 Medical Waste from self-quarantine has not been effective since its application is still low, and local drop boxes were not available as temporary shelters for B3 waste.